2003
DOI: 10.2337/diacare.26.12.3288
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of Solitary Islet Transplantation for Type 1 Diabetes Using Steroid-Sparing Immunosuppression

Abstract: OBJECTIVE -The aim of this study was to describe the National Institutes of Health's experience initiating an islet isolation and transplantation center, including descriptions of our first six recipients, and lessons learned.RESEARCH DESIGN AND METHODS -Six females with chronic type 1 diabetes, hypoglycemia unawareness, and no endogenous insulin secretion (undetectable serum Cpeptide) were transplanted with allogenic islets procured from brain dead donors. To prevent islet rejection, patients received daclizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(81 citation statements)
references
References 31 publications
1
80
0
Order By: Relevance
“…In summary, our data showed that islet transplantation results in improvement of selected aspects of QOL, and that there is little, if any, negative impact of the procedure, an important observation in view of the question as to whether chronic immunosuppression side effects might outweigh the benefits of improved metabolic control (21). We also show that re-introduction of insulin therapy is a fundamental independent variable that affects QOL outcomes, and we suggest that larger patient samples and longer follow-ups will strengthen our conclusions.…”
Section: Discussionmentioning
confidence: 53%
“…In summary, our data showed that islet transplantation results in improvement of selected aspects of QOL, and that there is little, if any, negative impact of the procedure, an important observation in view of the question as to whether chronic immunosuppression side effects might outweigh the benefits of improved metabolic control (21). We also show that re-introduction of insulin therapy is a fundamental independent variable that affects QOL outcomes, and we suggest that larger patient samples and longer follow-ups will strengthen our conclusions.…”
Section: Discussionmentioning
confidence: 53%
“…Human islets were prepared by the Cell Processing Unit, Department of Transfusion Medicine, National Institutes of Health (Hirshberg et al 2003a) Non-human primate islets from rhesus macaques were prepared by the Islet and Autoimmunity Branch of the NIH (Hirshberg et al 2002a,b). After isolation, human and nonhuman primate islets were shipped in CMRL media by overnight courier to Vanderbilt University and cultured for an additional 24 hr in CMRL media, 95% CO 2 /5% O 2 at 37C.…”
Section: Human and Non-human Primate Isletsmentioning
confidence: 99%
“…Life-threatening acute bleeds have been reported in islet recipients following the percutaneous approach (14)(15)(16) and this serious complication is potentially avoidable by obliteration of the intrahepatic portal catheter track.…”
Section: Introductionmentioning
confidence: 99%